Perspectives of Surgeons from Atlanta, USA. Issue 5 (14th October 2020) - Mohamed Ahmed, Eltayeb; Chen, Edward P.
Abstract: Background: The COVID‐19 pandemic in late 2019 quickly stretched health care system across the globe. Mortalities, shortages in health care system capacity, and lack of experience in similar circumstances required innovation in the way health care is delivered. Health care systems changed operating schedules, staff work pattern, and how patients are cared for. The effects of these changes reached patients, staff and training in different ways. Methods: We searched the Pubmed and EMBASE for articles related to COVID‐19. We also searched local emails and information provided to staff during the pandemic Results: The COVID‐19 pandemic affected organizations, patients, and staff. The organizations and staff had to adapt to the times to provide a safe and appropriate service to our patients. Conclusion: The pandemic challenged and changed the way we work as health care providers, and how we train the future surgeons. Changes in the system were effective.